2021
DOI: 10.1186/s12870-021-03017-2
|View full text |Cite
|
Sign up to set email alerts
|

Poplar aquaporin PIP1;1 promotes Arabidopsis growth and development

Abstract: Background Root hydraulic conductance is primarily determined by the conductance of living tissues to radial water flow. Plasma membrane intrinsic proteins (PIPs) in root cortical cells are important for plants to take up water and are believed to be directly involved in cell growth. Results In this study, we found that constitutive overexpression of the poplar root-specific gene PtoPIP1;1 in Arabidopsis accelerated bolting and flowering. At the ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 63 publications
(84 reference statements)
1
7
0
Order By: Relevance
“…Analysis of conserved domains indicated that EuPIP1;2 is a member of the PIP1 group and is most closely related to PIPs of dicotyledonous woody plants and only distantly related to PIPs of monocotyledonous plants. Previous studies have shown that PIP genes are expressed in diverse tissues of plants [32], such as roots, leaves, stems, inflorescences, fruits, and seeds [33]. In the present study, the expression level of EuPIP1;2 was highest in the fruit, followed by the root.…”
Section: Discussionsupporting
confidence: 56%
“…Analysis of conserved domains indicated that EuPIP1;2 is a member of the PIP1 group and is most closely related to PIPs of dicotyledonous woody plants and only distantly related to PIPs of monocotyledonous plants. Previous studies have shown that PIP genes are expressed in diverse tissues of plants [32], such as roots, leaves, stems, inflorescences, fruits, and seeds [33]. In the present study, the expression level of EuPIP1;2 was highest in the fruit, followed by the root.…”
Section: Discussionsupporting
confidence: 56%
“…One approach to achieve this goal is to overexpress the candidate AQP genes in gramineous crops, which may accelerate the glume opening process and maintain the lodicules swelling for longer time to enhance the pollination rate of the ovary for optimal hybrid seed production. Recent research on the poplar AQP gene PtoPIP1;1 has shown that the constitutive overexpression of it in Arabidopsis accelerated the flowering process of the transgenic plants ( Leng et al, 2021 ). However, further studies are required to comprehensively investigate the characteristics, specific functions, and regulatory mechanisms of these four candidate AQPs prior to the utilization of them.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Kong et al (2018) found that the transcripts of PIP and TIP subfamily members were highly abundant during flower opening stages in carnation ( Dianthus caryophyllus ). Recently, the constitutive overexpression of the poplar root-specific AQP gene PtoPIP1;1 in Arabidopsis has been reported to accelerate the flowering process of the transgenic lines ( Leng et al, 2021 ). All these pieces of research suggest the importance of AQPs in plant flowering.…”
Section: Introductionmentioning
confidence: 99%
“…The higher expression of AQPs in growth, compared to non-growing, tissues is often associated with higher cell hydraulic conductivity (Lp) in growing tissue [ 48 ]. PIPs play an important role in regulating rapid transmembrane water flow during plant growth and are believed to be directly involved in cell growth [ 49 ]. In this study, the transgenic lines assessed both showed significant increase in stomatal size and cell area.…”
Section: Discussionmentioning
confidence: 99%